Pengaruh Preheat, Postheat dan Kecepatan Las Proses Pengelasan Gas Metal Arc Welding (GMAW) Baja AISI 1050 terhadap Nilai Kekerasan - Rio Sandy; Viktor Naubnome; Reza Setiawan (Jurnal Teknik Mesin, 2022)
The purpose of this study was to determine the effect of preheat, reheating and welding speed on AISI 1050 steel using GMAW welding with a current of 130 A, a voltage of 20 volts, the preheat temperatures used were 250 C, 300 C, 350 C and reheating temperatures of 550 C, 600 C, 650 C, welding speed using automatic tools with speed variations of 2.5 mm/s, 4.5 mm/s, this study used an experimental method including preparation of tools and materials, specimen making, welding process and micro hardness testing of Vicker hardness later obtained The highest hardness result is 206.7 HV at a preheat temperature of 350 C plus a reheating temperature of 650 C with a welding speed of 2.5 mm/s and the lowest hardness value is at a preheat temperature of 300 C plus a reheating temperature of 600 C with a welding speed of 2.5 mm/s in the weldmetal, HAZ and base metal areas with the highest hardness values at a preheat temperature of 300 C plus a reheating of 600 C with a welding speed of 4.5 mm/s of 254.2 HV and 238.3 HV